Management staff of technical pedagogical universities – current situation and solutions - Nguyen, Văn Hùng (Journal of Technical Education Science, 2008)
The administrative body of the Universities of Technical Education has an important place and role to play in their good running and development. Actually the administration is composed for the most part of knowledgeable, well-experienced, trustworthy as well as politically sound personalities. These are however still rather limited as their capabilities in foreign language, informatics and their use of computer software are not highly efficient. A solution needs therefore to be found as regard their training and improvement